Space Weather, Environment and Societies - Lilensten, Jean; Bornarel, Jean (Springer Netherlands : Imprint: Springer, 2006)
Our planet exists within a space environment affected by constantly changing solar atmosphere producing cosmic particles and electromagnetic waves. This "space weather" profoundly influences the performance of our technology because we primarily use two means for transmitting information and energy; namely, electromagnetic waves and electricity. On an everyday basis, we have developed methods to cope with the normal conditions. However, the sun remains a fiery star whose 'angry' outbursts can potentially destroy spacecrafts, kill astronauts, melt electricity transformers, stop trains, and generally wreak havoc with human activities. Space Weather is the developing field within astronomy that aims at predicting the sun's violent activity and minimizing the impacts on our daily lives. Space Weather, Environment, and Societies explains why our technological societies are so dependent on solar activity and how the Sun disturbs the transmission of information and energy. Footnotes expand specific points and the appendices facilitate a more thorough command of the physics involved. This beautifully illustrated book is written for astronomy and nature enthusiasts as well as for the undergraduate/graduate level readers who would like to better master the physics of near space.